Diversity of Bivalvia Types in the Mangrove Area of Sungai Nyirih Village, West Kalimantan - Sofiana, Mega Sari Juane; Safitri, Ikha; Apriansyah, Apriansyah; Maulana, Adrian (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
Desa Sungai Nyirih, as one of the coastal villages in Jawai District, West Kalimantan, has the potential for a mangrove ecosystem with a diversity of aquatic biota, including bivalves. Most of the coastal communities in West Kalimantan catch and consume shellfish because it contains high nutrients. Therefore, shellfish can be an alternative source of animal protein. The aim of the study was to identify the genus of bivalves in the mangrove area of Desa Sungai Nyirih, Jawai District, West Kalimantan. The collection of bivalves was carried out using the exploratory method, as many as ±5 individuals of each genus were collected and all genera of bivalves were identified. The results showed that there were two genera found, such as the cockle (Geloina expansa) and the blood clam (Tegillarca nodifera).